Sex in the Garden: Consensual Encounters Gone Bad - Broyde, Michael J. (Wipf and Stock Publishers, 2019)
Intro -- Title Page -- About the Authors -- Preface -- Chapter 1: Introduction and Selected Excerpts from the Book of Genesis -- Chapter 2: Establishing a Framework -- Chapter 3: Human Sexuality -- Chapter 4: Marriage and Reproductive Issues -- Chapter 5: Sibling Rivalry -- Chapter 6: Why a Book of Genesis? -- Epilogue -- Bibliography.